Learning from Experience : Insights from China’s Progress in Disaster Risk Management - World Bank (World Bank, Washington, DC, 2020)
China has long known more than its fair share of disasters, including earthquakes, typhoons, floods, and droughts. The good news is that in recent decades, the country has made tremendous headway in building its resilience to disasters. Learning from these efforts will be critical to strengthening resilience building efforts in China and beyond. In that spirit, this Knowledge Note distills some lessons from China’s progress in many areas of disaster risk management. The note does not comprehensively cover the country’s achievements but focuses instead on topics that might be of interest to DRM practitioners globally. Drawing on expert insights from China’s disaster risk management community, key themes highlighted by this note include: the evolution of national disaster risk reduction (DRR) planning; the rise of demonstration communities; standardization of the disaster loss statistical system; development of an agricultural insurance system; establishment of a catastrophe risk insurance system. China has also made significant progress in establishing a catastrophe risk insurance system that allows for local innovations and pilots based on local characteristics; Development of a comprehensive space-based system of disaster and emergency monitoring. Amid a changing climate, China is facing the specter of even more significant disaster risks in the future, which may also bring global cascading impacts. Taking stock of the progress that has been achieved so far, there is good reason to believe that the country will continue to learn and innovate toward a resilient future.